CONSUMER PROTECTION FROM MISLEADING ADVERTISING ON THE TIKTOK DIGITAL PLATFORM: IBN TAIMİYAH'S PERSPECTIVE - Rabiatul Adawiyah Siregar; Zulham Zulham (Program Pascasarjana UIN Sumatera Utara, 2025)
The development of digital technology has led to the emergence of various social media platforms that are used as a platform for widespread and massive product marketing. TikTok, as one of the most popular short video platforms among children and students, has become a highly effective yet risky promotional platform. One serious issue that has emerged is the practice of misleading advertising targeting young consumers with manipulative content that does not align with product facts. This phenomenon is further complicated by TikTok's lack of full oversight by the Indonesian Broadcasting Commission (KPI), and the weakness of national regulations in reaching cross-border digital platforms. As a result, many children as consumers are vulnerable to falling victim to false information, fabricated testimonials, and exaggerated product promises. This study aims to analyze the phenomenon of misleading advertising on TikTok from the perspective of Ibn Taymiyyah, specifically regarding the concept of fraud (tadlis) and the urgency of moral protection for consumers. This research is a normative juridical study supported by empirical facts, namely analyzing positive legal principles through the approach of Ibn Taymiyyah's texts and supporting it with relevant field data regarding misleading advertising practices on TikTok. The results of this study emphasize the importance of state involvement in overseeing digital transactions to protect vulnerable parties, particularly children, from losses due to advertising fraud. The concept of hisbah, developed by Ibn Taymiyyah, serves as a normative reference in developing a consumer protection system in the digital era. Therefore, this study concludes by recommending that the Indonesian government immediately expand the scope of consumer protection regulations on digital platforms, establish a dedicated supervisory authority, and promote digital literacy based on Islamic values of honesty and moral responsibility. This way, consumer protection, particularly for children and students, can be enforced fairly and sustainably.